A Simple Ex Vivo Semiquantitative Fluorescent Imaging Utilizing Planar Laser Scanner: Detection of Reactive Oxygen Species Generation in Mouse Brain and Kidney. (2nd January 2019) - Hosoi, Rie; Sato, Sota; Shukuri, Miho; Fujii, Yuka; Todoroki, Kenichiro; Arano, Yasushi; Sakai, Toshihiro; Inoue, Osamu
Objective: Oxidative stress plays an important role in the onset of many neuronal and peripheral disorders. We examined the feasibility of obtaining semiquantitative fluorescent images of reactive oxygen species (ROS) generation in mouse brain and kidney utilizing a planar laser scanner and dihydroethidium (DHE). Methods: To investigate ROS generation in brain, sodium nitroprusside was injected into the striatum. Dihydroethidium was injected into the tail vein. After DHE injection, tissue slices were analyzed utilizing a planar laser scanner. For kidney study, cis-diamminedichloroplatinum [II] (cisplatin) was intraperitoneally administrated into mice. Results: Clear and semiquantitative fluorescent images of ROS generation in the mouse brain and kidney were obtained. Furthermore, the fluorescence intensity was stable and not affected by fading. Sodium nitroprusside induced approximately 6 times the fluorescence accumulation in the brain. Cisplatin caused renal injury in all mice, and in comparison with control mice, more than 10 times fluorescence accumulation was observed in the renal medulla with tubular necrosis and vacuolization. Conclusions: We successfully obtained ex vivo semiquantitative fluorescent images of ROS generation utilizing a planar laser scanner and DHE. This simple method is useful for ROS detection in several ROS-related animal models and would be applicable to a variety of biochemical processes.